Effect of functional stabilization training on balance and motor patterns in a patient with Charcot-Marie-Tooth disease - Kobesova, Alena; Kolar, Pavel; Mlckova, Jindriska; Svehlik, Martin; Morris, Craig E; Frank, Clare; Lepsikova, Magdalena; Kozak, Jiri (Neuro endocrinology letters, 2012)
OBJECTIVES: Balance and motor disturbances are significant symptoms commonly associated with hereditary motor and sensory neuropathy (HMSN), also known as Charcot-Marie-Tooth disease (CMT). Although CMT is a progressive neurological disease, comprehensive physiotherapeutic strategies may improve balance and motor patterns, and, therefore, enhance the quality of life (ADL). CASE PRESENTATION: A 55-year-old HMSN patient with confirmed CMT X phenotype was evaluated for locomotor stability on a stabilometric platform. Stability tests were repeated after a 3-week, intensive in-patient rehabilitation program and the results were compared. CONCLUSIONS: Improvements in "modified clinical testing of sensory interaction on balance", "limits of stability" and "forward lunge" tests were observed. Subjectively, the patient noted a significant improvement in both balance and gait.
Keywords: Charcotova-Marieova-Toothova nemoc; Humans; lidé; Quality of Life; fenotyp; kvalita života; Phenotype; Charcot-Marie-Tooth Disease